2016
DOI: 10.1080/09537287.2016.1217571
|View full text |Cite
|
Sign up to set email alerts
|

Information systems project failure – analysis of causal links using interpretive structural modelling

Abstract: The analysis of the root causes of information Systems (IS) project failure has been the subject of intense scrutiny for some time within industry and the academic community. Researchers have developed various models, notions of failure and categorizations to succinctly classify project failure into a set of key factors for organizations and project managers to focus on in their attempts to avoid failure. This study incorporates a technique titled: Interpretive Structural Modelling (ISM) as the methodology to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 78 publications
0
79
0
2
Order By: Relevance
“…This provides the room for future work of expanding the scope of the approach employed in this research to incorporate the technology adoption aspects and models (see for example, Dwivedi et al 2017a, b;Rana and Dwivedi 2015;Rana et al 2016Rana et al , 2017. This is particularly important as a large number of IS/IT projects fail (Dwivedi et al 2014;Hughes et al 2016Hughes et al , 2017 due to lack of adoption and use of technologies and/or applications in question.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…This provides the room for future work of expanding the scope of the approach employed in this research to incorporate the technology adoption aspects and models (see for example, Dwivedi et al 2017a, b;Rana and Dwivedi 2015;Rana et al 2016Rana et al , 2017. This is particularly important as a large number of IS/IT projects fail (Dwivedi et al 2014;Hughes et al 2016Hughes et al , 2017 due to lack of adoption and use of technologies and/or applications in question.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…This could provide a useful prescription for policymakers to implement in addition to consideration of this research. Moreover, the researchers could also consider implementing ISM methodology (Al-Muftah et al 2018;Dwivedi et al 2017a;Hughes et al 2016;Janssen et al 2018) to understand the driving and dependent barriers. The citizens are one of the most important stakeholders of such developments.…”
Section: Limitations and Future Scopementioning
confidence: 99%
“…The citizens are one of the most important stakeholders of such developments. Hence, in order to avoid resistance from stakeholders and failure of such initiatives Hughes et al 2016Hughes et al , 2017, the perceptions of citizens and government employees towards various aspects of smart cities should also be explored by utilising established theories and models (see for example, AlAlwan et al 2017;Dwivedi et al 2011aDwivedi et al , 2011bDwivedi et al , 2013Dwivedi et al , 2016Dwivedi et al , 2017bDwivedi et al , 2017cHossain and Dwivedi 2014;Kapoor et al 2014aKapoor et al , 2014bKapoor et al , 2015Rana and Dwivedi 2015;Rana et al 2015aRana et al , 2015bRana et al , 2016Rana et al , 2017Shareef et al 2011Shareef et al , 2016aShareef et al , 2016bShareef et al , 2017Sinha et al 2017;Slade et al 2015;Veeramootoo et al 2018;Weerakkody et al 2013Weerakkody et al , 2017) from information systems and electronic government domains.…”
Section: Limitations and Future Scopementioning
confidence: 99%
“…Ten out of 18 (56%) respondents suggested that challenged IS projects registered increasingly slow progress as issues were postponed and deadlines were not strictly adhered to. This issue of scope and adherence to deadlines has featured in other projects (Hughes et al, 2016). One of our interviewees pointed out that:…”
Section: Slow Progress and Schedule Violationmentioning
confidence: 89%